Implementasi Peraturan Bupati Asahan Nomor 67 Tahun 2018 Dalam Rangka Meningkatkan Ketertiban Berlalu Lintas Di Kawasan Kota Kisaran - Alfi Kurniawan; Syafrizal Syafrizal (Universitas Muhammadiyah Sumatera Utara, 2023)
The implementation of the Asahan Regent's Regulation Number 67 of 2018 concerning the Use of Road Networks and Traffic Flow Movements in the Kisaran City Area is a description of the non-optimal effectiveness of the use of road networks and traffic flow movements in Kisaran City. In practice, this policy has been implemented but has not been fully maximized because there are still several problems, such as the number of people who violate the traffic signs that have been set and the number of street vendors who are still selling on the road. This study aims to find out and describe in detail how the implementation of the Asahan Regent's Regulation Number 67 of 2018 concerning the Use of Road Networks and Traffic Flow in the Kisaran City Area. The research method used is a descriptive research method with a qualitative approach. Data collection techniques were carried out by means of interviews, observations and documentation related to the Implementation of the Asahan Regent Regulation Number 67 of 2018 concerning the Use of Road Networks and Traffic Flow in the Kisaran City Area. Based on the results of the study, it is known that the implementation of the Asahan Regent's Regulation Number 67 of 2018 concerning the Use of Road Networks and Traffic Flow in the Kisaran City Area is still not fully operational, this is indicated by the number of people who do not obey the traffic regulations that have been set by the government. The lack of public awareness in obeying the regulations that have been set has made this implementation not run optimally, even though the implementers of this policy have socialized to the public regarding traffic rules. In addition, with supervision that is still lacking and weak sanctions do not cause a deterrent effect to people who violate the traffic rules.Â